EFFECT OF GLYCAEMIC STATUS ON LEFT VENTRICULAR DIASTOLIC FUNCTION IN NORMOTENSIVE TYPE 2 DIABETIC PATIENTS - ullah, Hameed; Faheem, Muhammad; Bahadar, Sher; Hafizullah, Muhammad; Najeeb, Shahzad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Diabetes is associated with Left ventricular diastolic and systolic dysfunction known as diabetic cardiomyopathy. Echocardiography is helpful for the detection of diastolic dysfunction and Echocardiographic screening for asymptomatic diabetic cardiomyopathy should be performed in all asymptomatic diabetic subjects. Identification of diabetic cardiomyopathy should result in the initiation of therapies to prevent the progression of diabetic cardiomyopathy. The objectives of this Descriptive case series was to determine the effect of glycaemic status on left ventricular diastolic function in normotesive type 2 diabetic patients. Methods: This study was performed at Cardiology department, PGMI Lady Reading Hospital, Peshawar from March 2007 to September 2007. Sixty normotesive type 2 diabetic patients were enrolled, 20 well control, 20 moderately control and 20 poorly control (Group- 3). Main outcome measures was Left ventricular diastolic function determined by Echocardiography. Results: Out of 60 patients there were 32 (53.3%) males and 28 (46.7%) females. Mean E/A ratio in Group 1 was 1.38ï‚±0.29, in Group 2 was 1.16ï‚±0.39 and in Group 3 was 0.60ï‚±0.15 (p<0.05). IVRT in Group-1 was 91ï‚±7.87 mSec, in Group-2 was 100ï‚±7.83 mSec and in Group-3 was 109ï‚±6.45 mSec (p<0.05). DT in Group 1 was 207.2±12.6 mSec, in Group 2 was 218ï‚±11.3 mSec and in Group 3 was 229.7±9.52 mSec (p<0.05). Mean Em at mitral annulus in Group-1 was 0.14±0.04 m/Sec, in Group-2 was 0.11±0.04 m/Sec and in Group-3 was 0.10±0.03 m/Sec (p=0.002). Left ventricular diastolic dysfunction was documented in 4 (25%) patients in Group-1, 9 (45%) patients in Group-2 and 16 (80%) patients in Group-3 (p<0.05). There was Strong correlation between HbA1c level and diastolic indexes (p<0.05). Conclusion: Diastolic dysfunction is more frequent in poorly controlled diabetic patients and its severity is correlated with glycaemic control. Keywords: Type 2 diabetes mellitus, left ventricular diastolic function, Deceleration time